The relationship between gut microbiota, chronic systemic inflammation, and endotoxemia in patients with heart failure with preserved ejection fraction - A. N. Kaburova; O. M. Drapkina; S. M. Yudin; A. A. Yafarova; S. N. Koretsky; M. S. Pokrovskaya; V. V. Makarov; S. A. Kraevoy; B. B. Shoibonov; I. A. Efimova; Z. Z. Serebryanskaya (Кардиоваскулярная терапия и профилактика)
Aim. To study the relationship between the abundance of the genera in the gut microbiota (GM) and levels of serum biomarkers of chronic systemic inflammation and endotoxemia in patients with HFpEF.Material and methods. The composition of GM among 42 patients with HFpEF (men, 57,1%) was assessed by 16S rRNA sequencing. The median age was 67,0 years, interquartile range [64,0; 71,5] years. Correlation and multivariate regression analysis (with adjustments for sex and age) of relationships between the relative abundance of intestinal bacteria and the concentrations of serum biomarkers including high-sensitivity C-reactive protein (hsCRP), interleukins (IL) 1β and 6, the soluble suppressor of tumorigenicity (sST2), and the level of lipopolysaccharide (LPS) was carried out.Results. According to multivariate regression analysis, the relative abundance of Haemophilus was directly related to the concentration of IL-1β (odds ratio (ОR) 32,37, 95% confidence interval (CI) 2,071237,69, p=0,025), Coriobacteriaceae (unclassified) — with IL-6 (ОR 6,27, (1,42-36,74), p=0,024), Porphyromonadaceae (unclassified) — with sST2 (ОR 5,96, (1,33-34,39), p=0,028), and the relative abundance of the genera Pseudomonas (ОR 7,09, (1,45-42,39), p=0,020), Parasutterella (ОR 4,55, (1,07-22,76), p=0,047) and Clostridiaceae (unclassified) (ОR 4,85, (1,06-24,7), p=0,045) was directly associated with LPS levels.Conclusion. In patients with HFpEF, the relative abundance of some GM genera (e.g., Haemophilus, Coriobacteriaceae (unclassified), Porphyromonadaceae (unclassified), Pseudomonas, Parasutterella, Clostridiaceae (unclassified)) is statistically significantly associated with the concentration of biomarkers of chronic systemic inflammation and endotoxemia.